El mercado de las hierbas estivales en la montaña noroccidental leonesa durante el siglo XVIII (Estudios humanísticos. Geografía, historia y arte, 1995)
At the end of the 18th century town councils and monasteries that owned mountain, passes started long lawsuits against transhumant cattle raisers in order to evict them from the summer pastores that they had been enjoying up to then. In that way they expected the price of their fields to go up.